Catastrophic metallosis after tumoral knee prosthesis failure: A case report - La Verde, Luca (Int J Surg Case Rep, 2016)
INTRODUCTION: Metallosis is a condition characterized by an infiltration of periprosthetic soft tissues and bone by metallic debris resulting from wear or failure of joint arthroplasties. PRESENTATION OF CASE: Authors describe a case of a 45-year-old man treated for an osteosarcoma of the distal femur with a modular prosthesis when he was 18 years old, he developed massive metallosis with skin dyspigmentation after 17 years. His medical\surgical history was remarkable for a left tumoral knee prosthesis implanted 21 years ago. Two years before revision, the patient had a car accident with a two-points prosthesis breakage and despite the surgeon’s advice, the patient refused surgery. In two years, prosthesis malfunction caused a progressive catastrophic soft tissues infiltration of metallic debris. DISCUSSION AND CONCLUSION: Authors suggest that if prosthesis fracture is detected, revision surgery should be attempted as earlier as possible.